Energy harvesting from aerodynamic instabilities: Current prospect and future trends - Bashir, Musavir; Rajendran, Parvathy; Khan, Sher Afghan (IOP Publishing, 2018)
This paper evaluates the layout and advancement of energy harvesting based on aerodynamic instabilities of an aircraft. Vibration and thermoelectric energy harvesters are substantiated as most suitable alternative low-power sources for aerospace applications. Furthermore, the facility associated with the aircraft applications in harvesting the mechanical vibrations and converting it to electric energy has fascinated the researchers. These devices are designed as an alternative to a battery-based solution especially for small air-crafts, wireless structural health monitoring for aircraft systems, and harvester plates employed in UAVs to enhance the endurance and operational flight missions. We will emphasize on various sources of energy harvesting that are designed to come from aerodynamic flow-induced vibrations, specific attention is then given at those technologies that may offer, today or in the near future, a potential benefit to reduce both the cost and emissions of the aviation industry. The advancements achieved in the energy harvesting based on aerodynamic instabilities show very good scope for many piezoelectric harvesters in the field of aerospace, specifically green aviation technology in the future.